Problems of Islamic Education in the Era of the Industrial Revolution 5.0 - Mansir, Firman; Limbong, Effendi; Nukhba, Ghulam Mustafa; Rizapoor, Habiburrahman (Graduate School of UIN Syarif Hidayatullah Jakarta, 2023)
The construction of Islamic education is a gateway for the growth of human civilization and is expected to provide definite answers to society's problems. The problem of disintegration between sciences results in the compartmentalization of the human mind, personalities that are not characterized by divine values and tend to justify all means due to hedonism that plagues life. The problems of Islamic education in responding to the progress of the times, especially in the era of the industrial revolution 5.0 currently aimed at the challenges of Islamic educational institutions in the face of the destruction of the next generation of the nation's character. This is in line with the goal of Islamic education to create a generation of the nation that has the ability in terms of science and technology without eliminating the moral aspects of students. This research method uses a qualitative approach with data collection through literature studies that are analyzed by content analysis. The results showed that one of the challenges faced by Islamic education is the aspect of education management, future education planning has three characteristics of society, namely the future of sociology and the future of technology. Therefore, Islamic education is required to be able to balance itself with the progress of modern times or globalization that will continue to change. Islamic education must be able to show education that is responsive to the times. Preparing for the future of education is to advance, with an emphasis on quality, justice, prosperity, and so on.